The Effect of Mutual Coupling on a High Altitude Platform Diversity System Using Compact Antenna Arrays - Tommy Hult; Abbas Mohammed (International Journal of Antennas and Propagation)
We analyze the destructive effects of mutual coupling and spatial correlation between the separate antenna elements on a combined diversity system consisting of multiple HAPs (High-Altitude Platforms) employing various compact MIMO (Multiple-Input Multiple-Output) antenna array configurations, in order to enhance the mutual information in HAP communication links. In addition, we assess the influence of the separation angle between HAPs on system performance, and determine the optimal separation angles that maximize the total mutual information of the system for various compact MIMO antennas. Simulation results show that although the mutual information is degraded by mutual coupling and spatial correlation, the proposed HAP diversity system still provides better performance compared to a nondiversity system for all tested scenarios.